![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(7x-19\right)-\left(5x-12\right)=3x-\left(9-2x\right)-1\)
\(\Leftrightarrow7x-19-5x+12=3x-9+2x-1\)
\(\Leftrightarrow-3x=3\)
\(\Leftrightarrow x=-1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
|7x-3|-12=45-100
<=> |7x-3|-12=-55
<=> |7x-3|=-43
=> PT vô nghiệm vì |7x-3| >=0 với mọi x
|2x-7|-|7-5x|=0
<=> |2x-7|=|7-5x|
<=> \(\orbr{\begin{cases}2x-7=7-5x\\2x-7=-7+5x\end{cases}\Leftrightarrow\orbr{\begin{cases}2x+5x=7+7\\2x-5x=-7+7\end{cases}\Leftrightarrow}\orbr{\begin{cases}7x=14\\-3x=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=2\\x=0\end{cases}}}\)
Vậy x=2; x=0
![](https://rs.olm.vn/images/avt/0.png?1311)
a)4.(x+3)-(2x-12)=x-(-11+4)
4x+12-2x+12=x+11-4
2x+24=x+7
2x-x=-24+7
x=-17
b)-(4x-13)+(5x-4)=-3-(-15+7)
-4x+13+5x-4=-3+15-7
(-4x+5x)+13-4=12-7
x+9=5
x=-4
c)(5x-3)-(-2x+4)=6x-12
5x-3+2x-4=6x-12
5x+2x-6x=3+4-12
x=-5
d)(15x+20)-(9x-3)=5x-(-12)
15x+20-9x+3=5x+12
15x-9x-5x=-20-3+12
x=-11
e,(7x+14)+(3x-8)=-(-9x+3)
7x+14+3x-8=9x-3
7x+3x-9x=-14+8-3
x=-9
![](https://rs.olm.vn/images/avt/0.png?1311)
*) (-7) - (-12) + (-5)
= [(-7) + (-5)] + 12
= (-12) + 12
= 0
*) (-2) . 32 + 7 . (-4) - (-34)
= (-2) . 9 + (-28) + 34
= -18 + (-28) + 34
= -46 + 34
= -12
*) 12 . (-82) + (-12).18
= (-12) . 82 + (-12) . 18
= (-12) . (82 + 18)
= (-12) . 100
= -1200
![](https://rs.olm.vn/images/avt/0.png?1311)
=> 7x/12 + 5x/12 = 5/8 +3/8
=> 12x/12 =8/8=1
12x =12
x= 12:12 =1
![](https://rs.olm.vn/images/avt/0.png?1311)
a, 117 - \(x\) = 28 - (-7)
117 - \(x\) = 28 + 7
117 - \(x\) = 35
\(x\) = 117 - 35
\(x\) = 82
b, \(x\) - (-38 - 2\(x\)) = (-3) - 8 + 2\(x\)
\(x\) + 38 + 2\(x\) = - 11 + 2\(x\)
3\(x\) + 38 = - 11 + 2\(x\)
3\(x\) - 2\(x\) = - 11 - 38
\(x\) = - 49
![](https://rs.olm.vn/images/avt/0.png?1311)
a. -12 + x = 5x - 20
<=> 4x = 8
<=> x = 2
b. 7x - 4 = 20 + 3x
<=> 4x = 24
<=> x = 6
c. 5x - 7 = -21 - 2x
<=> 7x = -14
<=> x = -2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 5x - x = 40 + 16
4x = 56
x = 14
b) -12 + 20 = 5x - x
8 = 4x
x = 2
c) 7x - 3x = 20 + 4
4x = 24
x=6
a) 5x-16=40+x
<=> 4x = 56
<=> x = 14
b) -12+x=5x-20
<=> 4x = 8
<=> x = 2
c) 7x-4=20+3x
<=> 4x = 24
<=> x = 6
\(7x-\left(5x-12\right)=-34\)
\(\Rightarrow7x-5x+12=-34\)
\(\Rightarrow2x=-34-12\)
\(\Rightarrow2x=-46\)
\(\Rightarrow x=-23\)
Vậy x=-23